STRATEGI PENGEMBANGAN USAHA CEMILAN MARNING JAGUNG DI KOTA KUPANG - Mariana Djamituka; Tomycho Olviana; Santhy Chamdra (Buletin Ilmiah Impas, 2023)
This study aims to determine the internal and external factors that influence the development of a corn marning business, and an alternative strategy for developing a corn marning business at the Tibers Production House. The location of the research was carried out with the case study method. The data used consists of primary and secondary data. Analysis of the data used is descriptive analysis by describing the internal and external environment. Then formulate a development strategy using SWOT analysis (IFAS-EFAS analysis, SWOT matrix, and SWOT quadrant). The results showed that the internal and external factors that influenced the development of the corn marning business at the Tibers Production House were internal factors consisting of strengths, namely: quality products, low prices, strategic locations, skills in management and adequate workforce. While the weaknesses are, they have never participated in an exhibition, the promotion strategy is still simple, the management is not well organized and the equipment is limited. Meanwhile, external factors that include opportunities are: market demand, technological developments, improving the family economy, cooperation with partners, and government support. While the threats are the emergence of many new competitors, weather factors, high prices of raw materials, and the Covid-19 pandemic. The alternative strategy for developing corn marning business at the research location at the Tibers Production House business in Kupang City is more focused on the turn around strategy. Turn around strategy is a strategy where the company backs off from previous wrong decisions, and changes the company's position from loss to profitability. The WO (Weakness-Opportunities) strategy aims to improve internal weaknesses by taking advantage of external opportunities.